Uncertainty in Climate Change Research An Integrated Approach - Mearns, Linda O.; Forest, Chris E.; Fowler, Hayley J.; Lempert, Robert; Wilby, Robert L.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This edited volume with open access discusses all aspects of uncertainty in climate change research, with a unique emphasis on decision making under uncertainty and the assessment of various uncertainties in the landscape of decision making. By analyzing uncertainty through the lens of decision making, the book seeks to understand and assess the various uncertainties inherent in climate change research, including uncertainties in economic impacts, human health and vulnerability, fluctuations in the physical climate system, changes in infrastructure, and future climate projections. Very little published material exists on the uncertainties regarding vulnerability of different populations to climate change, and so the book characterizes the uncertainty in vulnerability to better formulate solutions to climate change problems in affected populations. The volume will be of interest to students, post-docs, early career scientists, and researchers interested in all aspects of climate change. After an introduction that addresses the issue of uncertainty in general as it pertains to climate change research, the book is divided into 5 main sections. Section 1 focuses on uncertainty in policy and decision making, and how climate-related policy choices impact risk management, impact mitigation, and adaptation. Section 2 discusses uncertainty in climate change impacts, including impacts in agriculture, water resources, transportation infrastructure, and human health and vulnerability. Section 3 analyzes physical climate uncertainties, such as Earth system projections, emissions concentrations, and sea-level rise projections. Section 4 details the methods for quantifying uncertainty from a statistical perspective. Section 5 concludes the volume with discussions on special topics and integrated themes on uncertainty, including ethics and uncertainty, communication, the economics of climate change, and integrated modeling for decision support.
Chapter 1: Integrated Uncertainty: An Introduction -- Chapter 2: Laying The Policy Groundwork For Considering Integrated Uncertainty -- Chapter 3: Climate Informed Decision Analysis Via Decision Scaling -- Chapter 4: Supporting Climate-Related Decisions Under Uncertainty -- Chapter 5: The Policy Portfolio Problem -- Chapter 6: Climate Change Adaptation In Practice: Navigating Uncertainty In The Real World -- Chapter 7: Uncertainty of Climate Change Impacts On Crop Production -- Chapter 8: Uncertainty In Ecological Models -- Chapter 9: Uncertainty In Hydrologic And Water Resources Modelling -- Chapter 10: Dimensions of Uncertainty In Mitigating Flooding -- Chapter 11: Uncertainty In Transportation Infrastructure -- Chapter 12: Science In Coastal Adaptation Decision-Making: Working Effectively With Persistent Uncertainties -- Chapter 13: Uncertainty In Determining Impacts of Climate Change On Human Health -- Chapter 14: Uncertainty And Socioeconomic Vulnerability To Climate Change -- Chapter 15: Climate/Earth System Projections And Their Uncertainties: An Overview -- Chapter 16: Emissions And Concentration Scenarios -- Chapter 17: The Importance of Internal Variability For The Uncertainty In Climate Change Projections And Decision Making -- Chapter 18: Downscaling Future Climate Projections: Compounding Uncertainty But Adding Value? -- Chapter 19: Characterizing The Uncertainty Surrounding Sea-Level Projections To Inform Decisions -- Chapter 20: Uncertainty Quantification: A Statistical Perspective -- Chapter 21: Uncertainty And Extremes -- Chapter 22: How Uncertainty Interacts With Ethical Values In Climate Change Research -- Chapter 23: Expert Judgment And Communication of Uncertainty.-Chapter 24: Uncertainty In The Economic Appraisal of Adaptation -- Chapter 25: Uncertainty Management In A Decision Context: What We Learned From The Decision Center For A Desert City -- Chapter 26: Acting With Uncertainty: Reflecting On A Decade of Rapid Progress In Climate Policy, Research And Practice.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Environment; Physical geography; Human ecology -- Study and teaching; Environmental Sciences; Earth System Sciences; Environmental Studies; Earth System Sciences; Earth System Sciences